2020
DOI: 10.3390/ijms21155433
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide Has Negative Effects on In Vitro Enhanced Osteogenic Phenotypes by Inflammatory Cytokine TNF-α via Inhibiting JNK Signaling

Abstract: Nuclear factor kappa B (NF-κB) regulates inflammatory gene expression and represents a likely target for novel disease treatment approaches, including skeletal disorders. Several plant-derived sesquiterpene lactones can inhibit the activation of NF-κB. Parthenolide (PTL) is an abundant sesquiterpene lactone, found in Mexican Indian Asteraceae family plants, with reported anti-inflammatory activity, through the inhibition of a common step in the NF-κB activation pathway. This study examined the effects of PTL o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Interestingly, PTL increased cell viability and inhibited H2O2induced apoptosis, indicating its role in inhibiting oxidative stress and cellular apoptosis in osteoblasts (Mao and Zhu, 2018). However, more recently, PTL was found to reduce the activity of ALP, alizarin red-positive mineralization, and the expression of ALP and osteocalcin mRNA using human periosteum-derived cells (hPDCs) (Park et al, 2020). In addition, PTL also attenuated the increased osteoblastic differentiation of TNF-α -treated hPDCs via the suppression of JNK signalling (Park et al, 2020).…”
Section: The Role Of Ptl In Skeletal Disordersmentioning
confidence: 99%
“…Interestingly, PTL increased cell viability and inhibited H2O2induced apoptosis, indicating its role in inhibiting oxidative stress and cellular apoptosis in osteoblasts (Mao and Zhu, 2018). However, more recently, PTL was found to reduce the activity of ALP, alizarin red-positive mineralization, and the expression of ALP and osteocalcin mRNA using human periosteum-derived cells (hPDCs) (Park et al, 2020). In addition, PTL also attenuated the increased osteoblastic differentiation of TNF-α -treated hPDCs via the suppression of JNK signalling (Park et al, 2020).…”
Section: The Role Of Ptl In Skeletal Disordersmentioning
confidence: 99%
“…A total of 13 different cell lines originated from humans, mice, and rats were evaluated in the studies ( Figure 3 ). Among them, four cells were cancer cell lines including, mice melanoma B16 cells ( Ye et al, 2011 ), human HL-60 cell line ( Choi et al, 2002 ; Kim et al, 2005 ; Kim et al, 2006 ; Kweon et al, 2015 ), human CML cell line K562 ( Huang et al, 2016 ; Cai et al, 2017 ), human AML cell line U937 ( Huang et al, 2016 ), three cells were stem cells including rat mesenchymal stem cell ( Li et al, 2012 ), mice mesenchymal stem cells C3H10T1/2 ( Kim et al, 2017 ), hematopoietic stem and progenitor cells (HSPCs) ( de Lichtervelde et al, 2013 ), and six cells were normal cell lines including, 3T3-L1 cell line ( Galvis et al, 2011 ; Jang, 2016 ; Kim et al, 2016 ; Abood et al, 2018 ; Kwak and Kim, 2019 ), mice bone marrow macrophage ( Cheon et al, 2014 ; Hu et al, 2019 ; Lee et al, 2019 ; Li et al, 2019 ; Zhou et al, 2019 ; Lu et al, 2020 ), CD4 + T cell ( Park et al, 2016 ), human periosteum-derived cells ( Park et al, 2020 ), human preadipocytes ( Jang, 2016 ), mice MC3T3-E1 cell line ( Kim et al, 2017 ). All cell lines except the murine melanoma B16 cell line had a mesodermal origin.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, the results of all studies were in line with their objectives, either inhibiting or inducing effects. Only some studies ( Kim et al, 2006 ; Jang, 2016 ; Park et al, 2020 ) reported the negative results, which were either evaluating and comparing the effects of other sesquiterpene lactones or non-lactone derivatives, or the primary objective of the study was not evaluating the differentiation. Moreover, the occurrence of reverse effects was not reported in any studies.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings showed that irAEs in high-risk groups may be more sensitive to methotrexate treatment. Parthenolide is one of the biologicals that play an anti-inflammatory role by inhibiting nuclear factor kappa B (NF-κB) and cytokine tumor necrosis factor (TNF)-α [49,50]. Parthenolide can induce lung cancer cells apoptosis and inhibit human lung cancer cell growth [51][52][53], demonstrated anticancer activity in the treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 99%